Pengembangan Literasi Emergen Pada Anak Usia Dini - Lathifatul Fajriyah (Proceedings of The ICECRS, 2018)
Emergent Literacy is a concept used to prepare child literacy before entering elementary school. The purpose of this study is to develop emergency literacy by providing stimuli that can develop children's literacy. There are two domains of emergent literacy ie inside-out and outside-in. These two domains cannot be separated because they will help the child in the emergence literacy process in early childhood. As for the efforts that can be done to develop the emergent literacy in early childhood is to prepare the literacy environment and read the story. Various studies say that by telling the story of children learn various activities that can develop literacy.